Metallic materials properties development and standardization (MMPDS) : MMPDS-08, April 2013. (Federal Aviation Administration ; Battelle Memorial Institute [distributor], 2013)
This document contains design information on the strength properties of metallic materials and elements for aircraft and aerospace vehicle structures. This is the replacement to MMPDS-07 and prior editions as well as the replacement for all editions of MIL-HDBK-5, Metallic Materials and Elements for Aerospace Vehicle Structures Handbook that was maintained by the U.S. Air Force. All information and data contained in this Handbook has been reviewed and approved in a standardized development process. The development and ongoing maintenance process involves certifying agencies, including the FAA, DoD, and NASA, and major material suppliers and material users worldwide. The data and procedures in this Handbook are continuously reviewed, and if needed, are modified or removed for consistency. With advances in materials and fastener systems, and with the review process of existing information, annual updates of the MMPDS are expected.